Analysis of The Level of Erosion Hazard in The Walanae Watershed and Land Conservation Directions to Reduce The Erosion Rate in The Walanae Watershed - Firdazam, Firdazam; Sangkawati, Sri; Wulandari, Dyah Ari (Ridwan Institute, 2023)
The Walanae Watershed (DAS) is one of the Walanae – Cenranae Sub Watersheds in several districts, including Wajo, Soppeng, Bone, and Maros regencies. The river flow in the Walanae watershed flows from south to north and empties into Lake Tempe, Wajo Regency. The condition of Lake Tempe, which continues to experience silting due to erosion and sedimentation, is still happening. This siltation resulted in sediment discharges reaching 519,000 m3/year. This siltation can cause a narrowing of the lake area and flooding around Lake Tempe. The purpose of this study is to model erosion control in the Walanae watershed to reduce the level of siltation that occurs in Lake Tempe. Analysis of the erosion rate of the Walanae watershed using the USLE method. The analysis results show that the erosion rate that occurred in 2000 was 187.52 Tons / Ha / Yr, while in 2022, it was 253.336 Tons / Ha / Yr. Scenarios based on land conservation actions can reduce the erosion rate by 149,034 tons/ha / Year. The scenario was carried out by considering slope classes and land cover in the Walanae watershed. In flat to gentle slope conditions, ground cover crops and livestock grazing are needed; in rice fields and dryland agriculture, rural and annuals and mulch reinforcement are needed. Conservation measures are needed in steep to very steep slope classes, such as bench terraces and plant cover crops for agricultural land cover. As for forest areas, permanent vegetation or agroforestry is needed.